Studi Kinetika Efektifitas Minyak Daun Cengkeh (Syzigium aromaticum) Sebagai Antifungi Candida albicans - Musta, Rustam; Nurliana, Laily (Indonesian Journal of Chemical Research, 2019)
Kinetic studies effectiveness clove leaf (Syzigium aromaticum) oil as antifungal Candida albicans have been done. The study have purpose to determine the reaction order, reaction constants (k) and relationship the concentration of clove leaf (Syzigium aromaticum) oil every time (At) with the initial concentration of of clove (Syzigium aromaticum) oil (Ao) and time (t) and equipped determination of the minimum concentration of clove leaf (Syzigium aromaticum)oil effective anti-fungus Candida albicans. The results shows the anti-fungal activity clove leaf (Syzigium aromaticum) oil on Candida albicans for each variation of the concentration 100%, 75%, 50% and 25% are 14.2 mm, 12.2 mm, 10.8 mm and 10.4 mm respectively. Reaction order as antifungal of the clove leaf (Syzigium aromaticum) oil on Candida albicans is 0.2112 with k = 5.0594. The minimum concentration of clove leaf (Syzigium aromaticum) oil as anti-fungal Candida albicans is 17.86%.